Have Climate Days Impacted Society (CONECT. International Scientific Conference of Environmental and Climate Technologies, 2026)
In Latvia, the “Climate Days in Schools” program is one of the major initiatives in climate education that aims to teach students about environmental issues, encourage the use of reliable information sources, and promote environmentally responsible behaviour. However, the factors that determine the program’s effectiveness and whether it influences students’ behaviour in the long term remain unclear. This research focuses on evaluating the impact of “Climate Days in Schools” on students’ attitudes and behaviour, with particular attention to teachers’ professional competence and the role of a competency-based education approach. It is assumed that the outcomes of climate education activities are closely connected to teachers’ ability to integrate climate issues into the teaching and learning process. This paper is based on a mixed-methods study. The research methods include a review of scientific literature on climate education, the role of teachers, and mechanisms of behavioural change. Empirical data are collected using a survey instrument. The survey is conducted with primary, lower secondary, and secondary school teachers whose students have previously participated in “Climate Days”. Several behavioural change indicators are examined, including energy saving, waste sorting, reuse of items, involvement in environmental initiatives, and environmentally responsible daily habits. It is expected that the results of the study will reveal a significant relationship between teachers’ professional competence, the implementation of a competency-based approach, and the long-term behavioural changes in students. Based on the findings, proposals for improving “Climate Days in Schools” in Latvia will be developed, including the creation of a regional implementation model and recommendations for providing more examples of effective educational practices. The findings may serve as a foundation for the further development of climate education and for strengthening education policy related to sustainable development.